Generation of a human induced pluripotent stem cell line, BRCi001-A, derived from a patient with mucopolysaccharidosis type I - Mika Suga; Takayuki Kondo; Keiko Imamura; Ran Shibukawa; Yasue Okanishi; Yukako Sagara; Kayoko Tsukita; Takako Enami; Mahoko Furujo; Kaoru Saijo; Yukio Nakamura; Mitsujiro Osawa; et al. (Stem Cell Research, 2019)
Mucopolysaccharidosis type I (MPS I) is a rare inherited metabolic disorder caused by defects in alpha-L-iduronidase (IDUA), a lysosomal protein encoded by IDUA gene. MPS I is a progressive multisystemic disorder with a wide range of symptoms, including skeletal abnormalities and cognitive impairment, and is characterized by a wide spectrum of severity levels caused by varied mutations in IDUA. A human iPSC line was established from an attenuated MPS I (Scheie syndrome) patient carrying an IDUA gene mutation (c.266G > A; p.R89Q). This disease-specific iPSC line will be useful for the research of MPS I.